Simulation of Coalescence, Breakup, and Mass Transfer in Polydisperse Multiphase Flows. Issue 7 (July 2014) - Renze, Peter; Buffo, Antonio; Marchisio, Daniele L.; Vanni, Marco; Nilles, Michael; Wozny, Günter
Abstract A two‐fluid model implemented in OpenFOAM is extended to account for the polydispersity of the disperse phase by coupling CFD with population balance models. The method is applied to predict the fluid dynamics and mass transfer in bubble columns. Here, the conditional quadrature method of moments is implemented in the open‐source code OpenFOAM for describing bubble coalescence, breakage, and mass transfer in two reference cases of rectangular bubble columns. The overall approach is accurate, efficient and robust, and therefore, suitable for the simulation of multiphase flows with industrial relevance.